Factors Associated with Inadequate Tissue Yield in EUS-FNA for Gastric SMT. (1st June 2011) - Suzuki, Takuto; Arai, Makoto; Matsumura, Tomoaki; Arai, Eiji; Hata, Sachio; Maruoka, Daisuke; Tanaka, Takeshi; Nakamoto, Shingo; Imazeki, Fumio; Yokosuka, Osamu
Abstract : Aims . Our aim was to identify the factors that made the specimens inadequate and nondiagnostic in endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) biopsy of suspected submucosal tumors (SMTs). Methods . From August 2001 to October 2009, 47 consecutive patients with subepithelial hypoechoic tumors originating in the fourth sonographic layer of the gastric wall suspected as GIST by standard EUS in Chiba University hospital underwent EUS-FNA for histologic diagnosis. We evaluated patient age, sex, location of lesion, size, pattern of growth in a stomach, and pattern of echography retrospectively. We defined a case of gaining no material or an insufficient material for immunohistological diagnosis as nondiagnostic. Results . The diagnostic yield of EUS-FNA for the diagnosis of gastric SMTs was 74.5%. Multivariate logistic regression analysis identified that age of under 60 years (compared with patients older than 60 years: odds ratio [OR] = 11.91, 95% confidence interval [CI] = 1.761–80.48) and location of SMT at lower third area (compared with upper or middle third area: OR = 10.62, 95% CI = 1.290–87.42) were the predictive factors for inadequate tissue yield in EUS-FNA. Conclusions . The factors associated with inadequate tissue yield in EUS-FNA were younger age and the location of lesion at lower third area in stomach.